BACKGROUND AND FACTORS OF BILATERAL APPROXIMATION OF THE REPUBLIC OF BELARUS AND THE RUSSIAN FEDERATION - Польовий, Т. Є. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article considers the first phase of the development of Belarusian-Russian contacts, which is marked by a low level of interaction between states and the lack of objective interest in the inter-state cooperation. In the course of the research it was found out that it was the Belarusian side which initiated the bilateral convergence, being led by its own economic and commercial interests, common historical past and cultural kinship of the two nations. However, the Russian side for a long time did not consider Belarus as an important international partner.